Transforming Agriculture through Cloud-Based Social Networking Applications - Lalita Devi Pila, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article explores the transformative impact of cloud-based social networking applications on agricultural practices, examining how these digital platforms are revolutionizing farmer communication, collaboration, and decision-making processes. It investigates various aspects of digital agricultural platforms, including real-time communication networks, knowledge exchange systems, collaborative problem-solving frameworks, data-driven management approaches, market intelligence tools, resource optimization strategies, and community development initiatives. Through analysis of multiple research studies and case implementations, the article demonstrates how these platforms enhance agricultural productivity, strengthen farming communities, and promote sustainable practices while addressing traditional challenges in agricultural extension and market access.
Keywords: Digital Agriculture; Cloud-based Platforms; Agricultural Innovation; Farming Communities; Sustainable Agriculture